1988
DOI: 10.1016/0378-1097(88)90332-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobactin-mediated iron uptake system in intestinal Escherichia coli

Abstract: SUMMARYEscherichia coli strains isolated from children with diarrhea were studied to determine the incidence of the components of the aerobactin system. The production of aerobactin and the presence of the aerobactin receptor were demonstrated using bioassay techniques. The presence and location of the genes for the aerobactin system was determined by colony and Southern DNA-DNA hybridization. It was found that aerobactin and the aerobactin receptor could be coded by either chromosomal or plasmid genes. A high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Further work is required to determine the distribution of Klebsiella strains expressing a functional aerobactin receptor without apparent aerobactin production. A high incidence of the aerobactin receptor in the absence of aerobactin production has been observed in E. coli strains isolated from children with diarrhoea (Fernandez-Beros et al, 1988). In these strains the receptor was located either on a plasmid or in the chromosome but in contrast to the klebsiellae described here, all cloacinsensitive strains hybridized with the pColV-K30 aerobactin gene probe (Fernandez-Beros et al, 1988).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Further work is required to determine the distribution of Klebsiella strains expressing a functional aerobactin receptor without apparent aerobactin production. A high incidence of the aerobactin receptor in the absence of aerobactin production has been observed in E. coli strains isolated from children with diarrhoea (Fernandez-Beros et al, 1988). In these strains the receptor was located either on a plasmid or in the chromosome but in contrast to the klebsiellae described here, all cloacinsensitive strains hybridized with the pColV-K30 aerobactin gene probe (Fernandez-Beros et al, 1988).…”
Section: Discussionmentioning
confidence: 82%
“…Since the first indications that the aerobactin iron-uptake system was associated with virulence, considerable efforts have been directed towards elucidating its distribution and genetic organization within virulent enteroinvasive, enteropathogenic and enterotoxigenic strains of E. coli (Griffiths, 1987;Roberts et al, 1986;Carbonetti et al, 1986;Fernandez-Beros et al, 1988;Marolda et al, 1987). This work has been extended to other enterobacterial pathogens including the Klebsiellae (Nassif & Sansonetti, 1986;Williams et al, 1987).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the 18 blood isolates containing ColV plasmids, 11 were chosen for further study. It was found that each of the ColV plasmids hybridized with the traT, iss, and iu DNA probes.…”
Section: Resultsmentioning
confidence: 99%
“…1984 [11]). The 100 strains isolated in 1982 to 1983 included 17 enterotoxigenic E. coli strains, 2 enteropathogenic E. coli strains, and one strain that produced Vero toxin.…”
Section: Methodsmentioning
confidence: 99%